1999
DOI: 10.2105/ajph.89.7.1066
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethnicity, family income, and parental education on children's health and use of health services.

Abstract: OBJECTIVES: This study characterized ethnic disparities for children in demographics, health status, and use of services; explored whether ethnic subgroups (Puerto Rican, Cuban, and Mexican) have additional distinctive differences; and determined whether disparities are explained by differences in family income and parental education. METHODS: Bivariate and multivariate analyses of data on 99,268 children from the 1989-91 National Health Interview Surveys were conducted. RESULTS: Native American, Black, and Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
131
6
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 25 publications
15
131
6
1
Order By: Relevance
“…In contrast, Mexican children were less likely to have an asthma diagnosis and the rates for these children were nearly at the national norm. This finding is consistent with observations from other studies (Mendoza et al, 1991;Flores et al, 1999). Our study found that the Mexican children were reported to have both fewer symptoms and lower rates of ETS and pets than other groups.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, Mexican children were less likely to have an asthma diagnosis and the rates for these children were nearly at the national norm. This finding is consistent with observations from other studies (Mendoza et al, 1991;Flores et al, 1999). Our study found that the Mexican children were reported to have both fewer symptoms and lower rates of ETS and pets than other groups.…”
Section: Discussionsupporting
confidence: 93%
“…[30][31][32][33][34][35][36] Sociodemographic variables included the child's age, gender, race/ethnicity, and insurance status. All these variables were originally categorical in NSCH, and we further grouped their categories for our study.…”
Section: Sociodemographic and Parental Covariatesmentioning
confidence: 99%
“…Because of the limited data on what factors may impact the HRQL of a child with sickle cell disease, a stepwise regression analysis was used as an exploratory tool to identify potentially important patient and disease factors associated with HRQL. The variables displayed in Tables I and II, all shown to affect HRQL previously (Flores et al, 1999;Asmussen et al, 2000;Kahn et al, 2002;Palermo et al, 2002;Mansour et al, 2003), were examined in the stepwise regression model as independent variables to determine their influence on HRQL.…”
Section: Factors Associated With Hrql In Children With Sickle Cell DImentioning
confidence: 99%
“…To gain a better understanding of HRQL in children with chronic illness, it is necessary to determine what factors influence HRQL. Among children with a chronic illness, HRQL is associated with the severity of their disease status as well as demographic factors (Flores et al, 1999;Asmussen et al, 2000;Kahn et al, 2002;Palermo et al, 2002;Schwimmer et al, 2003). In sickle cell disease, the factors that may impact the child's HRQL need to be explored further -only one prior study has examined such variables (Palermo et al, 2002).…”
mentioning
confidence: 99%